2020
DOI: 10.7717/peerj.10376
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for new-onset atrial fibrillation in patients with chronic obstructive pulmonary disease: a systematic review and meta-analysis

Abstract: Background New-onset atrial fibrillation (AF) in patients with chronic obstructive pulmonary disease (COPD) is associated with an accelerated decline in lung function, and a significant increase in mortality rate. A deeper understanding of the risk factors for new-onset AF during COPD will provide insights into the relationship between COPD and AF and guide clinical practice. This systematic review and meta-analysis is designed to identify risk factors for new-onset AF in patients with COPD, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…However, AF was less common among patients with a previous history of stroke, CABG, or PCI. Other studies have confirmed that these comorbidities are associated with adverse clinical outcomes due to atrial stiffness, vasoconstrictions, and inflammation [ 17 , 18 ]. Kazeminia et al reported that diabetes was the most common comorbidity among patients with heart failure, and the prevalence increases over time [ 19 ].…”
Section: Discussionmentioning
confidence: 95%
“…However, AF was less common among patients with a previous history of stroke, CABG, or PCI. Other studies have confirmed that these comorbidities are associated with adverse clinical outcomes due to atrial stiffness, vasoconstrictions, and inflammation [ 17 , 18 ]. Kazeminia et al reported that diabetes was the most common comorbidity among patients with heart failure, and the prevalence increases over time [ 19 ].…”
Section: Discussionmentioning
confidence: 95%
“…For example, some targeted treatments and medication usages will be emphasized in the novel handbook of COPD (and asthma) management. Some independent studies have substantially identified the increased cardiovascular risks in patients with COPD and asthma, and some associated evidence was provided by retrievable researches and reviews ( 9 , 10 ). However, no previous study provided enough quantitative synthesis evidence to identify the magnitude of the increased AF risk among patients with COPD or asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Romiti et al ( 9 ) reported that COPD was prevalent in 13% of patients with AF, and was associated with increased adverse effects, the burden of management, and poorer prognosis, with double times the possibility of all-cause death and death of cardiovascular diseases and major bleeding. Based on the study of Huang Q et al ( 10 ) various characteristics serve as the risk factors for AF development, such as older age, males, and white race. In the study of Lee et al ( 7 ), the progression and recurrence of AF were independently influenced by COPD, and the outcomes of COPD patients with AF were worsened than those of people with sinus rhythm.…”
Section: Introductionmentioning
confidence: 99%
“…Cox regression models were constructed to calculate the multivariable adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) of the incidence of Afib for each metabolic obesity phenotype compared to the MHNW group. Possible confounding factors according to general principles and reviews of previous studies (Feng et al 2019;Huang et al 2020;Kwon et al 2019;Lee et al 2017;Nystrom et al 2015;Vyssoulis et al 2013) were selected. Model 1 was adjusted for sex and age; model 2 was adjusted for all model 1 variables plus current smoking status, alcohol use, and regular exercise; model 3 was adjusted for all model 2 variables plus marital status, education level, and average monthly income.…”
Section: Methodsmentioning
confidence: 99%